Новый вид рода Polytoma Ehr. (Chlamydomonadaceae, Chlorophyta) - Демченко, Э.Н.; Михайлюк, Т.И. (Альгология, 2005)
Приведены латинский диагноз, описание, рисунки и микрофотографии нового для науки вида из рода Polytoma – P. loricatum Demchenko sp. nov., который был обнаружен в луже в летний период на территории г. Киева. Обсуждается вариабельность морфологических признаков нового вида и отличие его от известных видов данного рода, а также других родов бесцветных жгутиконосцев. Latin diagnosis, description, drawings and microphotographs of new species from the genus Polytoma: P. loricatum Demchenko sp. nov. are presented. The species was found in the summer rain pool in Kiev. Variability of morphological characters of new species and differences from the both known species of this genus and other genera of colorless flagellates are discussed.